2012
DOI: 10.1111/j.1740-8261.2012.01961.x
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL SIGNIFICANCE AND PROGNOSIS OF DEEP DIGITAL FLEXOR TENDINOPATHY ASSESSED OVER TIME USING MRI

Abstract: Deep digital flexor (DDF) tendinopathy is one of the most frequent causes of foot lameness and the prognosis is guarded. The progress of lesion healing may be followed by magnetic resonance (MR) imaging to formulate a prognosis and to adapt the rehabilitation program. We assessed the correlation of outcome with total tendon damage and temporal resolution of MR abnormalities. Images from 34 horses with DDF tendinopathy that had undergone at least two low-field standing MR examinations of the foot (mean 2.5 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 22 publications
1
53
2
Order By: Relevance
“…Horses with lesions longer than 35 mm or greater than 20 per cent of the tendon cross-sectional area invariably remained lame (Vanel and others 2012). Finally, the response to treatment has also begun to be documented.…”
mentioning
confidence: 99%
“…Horses with lesions longer than 35 mm or greater than 20 per cent of the tendon cross-sectional area invariably remained lame (Vanel and others 2012). Finally, the response to treatment has also begun to be documented.…”
mentioning
confidence: 99%
“…T2* GE should be used especially when looking for hyperacute blood, because it detects effects of methemoglobin and deoxyhemoglobin (Edelman 1986, Kidwell et al 2004. The value of T2* GE is limited in protocol for deep digital flexor tendon, while its signal is similar to T1 GE and does not significantly change during the process of healing (Vanel et al 2012). In standing low-field MRI basic protocol may consist of T1 GE, T2 FSE and STIR in sagittal, transverse and frontal planes (Mair and Kinns 2005).…”
Section: Artifactsmentioning
confidence: 99%
“…Maher et al (2011) have suggested that tendon lesions with increased signal on PD images without signal increase on STIR and T2w images can be associated with degeneration. What is more, this pattern is visible during early stages of injury, and can retain even months or years after tendon fiber disruption (Maher et al 2011). Vanel et al (2012 have assumed that STIR FSE sequence is the most reliable in deep digital flexor tendinopathy outcome and decreased signal was associated with lameness improvement.…”
Section: Pathologymentioning
confidence: 99%
“…The prognosis has also been effectively linked with the size of the tendon lesion. Horses with lesions longer than 35 mm or >20% of the tendon cross‐sectional area invariably remained lame , while those longer than 30 mm or >10% of tendon cross‐sectional area invariably did not return to previous levels of athletic activity.…”
mentioning
confidence: 99%